Directions for implementing the graphic style of the Armed Forces of Ukraine in the design of an electronic multimedia training manual on tactical training - Biziuk, A.V.; Zmiivska, N.G. (Radiotekhnika, 2024)
The main problems of introducing a graphic style in the visual communication of the Armed Forces of Ukraine into the design of an electronic multimedia training publication on tactical training were analyzed: the use of single colors for the structural formations of the Armed Forces of Ukraine for the design of all types of military publications; application for the development of design and layout of all types of media exclusively of one (basic) font UAF Sans. As a result of the conducted analysis, it was established that when developing the design of an electronic educational publication on tactical training, this approach does not fully meet the requirements for its compliance with the interests of the target audience and the connection with the subject matter of the material. Based on the experience of creating an electronic multimedia training manual "Tactical training (mechanized detachment)", a not quite successful implementation of the literal approach, in terms of requirements for the graphic style of the Armed Forces of Ukraine, was demonstrated when creating the color scheme of the main screen. The results of the research conducted by the team of marketers and designers of the dissidend creative agency on the study of the psychology of color and its impact on consumers of different ages and genders are presented, which confirm the inconsistency of the established colors with the preferences of the target audience – young people, mainly males. Ways to solve the problems of introducing the graphic style of the Armed Forces of Ukraine into the design of the electronic multimedia training manual "General Tactics (Mechanized Division)" are proposed, taking into account the topic of the publication and the interest of the target audience: using a combination of colors close in saturation to create a color gamut of the publication’s screens (creating a contrast in saturation ) "Uniform" and "Step" by the method of radial gradient filling of the background of the screens or the contrast of diametrically opposite colors: yellow, blue and green; application for emphasis when creating the typography of the basic communication font of the Armed Forces of Ukraine UAF Sans of various sizes and changing its drawings, creating italics using the features of the Figma program regarding the inclination of letters. As a result of the study, based on the proposed approaches, created examples of the cover and the main screen of the educational publication are presented.